Performative Discourse of Drag Queens: A Sociolinguistic Study - Szymańska, Maria (Research in Language, 2020)
The article presents the analysis of two speeches given by Rory O’Neill, also known as Panti Bliss, who is so far the most recognisable Irish drag queen. Apart from being a drag queen, Rory O’Neill is also a political activist whose performances were part of the campaign before the referendum concerning the 34th Amendment to the Constitution of Ireland. In the analysis both these aspects of the speaker’s identity are taken into consideration. Although the analysis is mostly linguistic, it also considers extralinguistic aspects of communication, e.g. the performer’s appearance on stage, as contextual elements are essential in sociolinguistic contexts. Thus, the analysis draws from the theoretical background focused on political discourse and the language used by drag queens to a detailed account of the two speeches in order discuss them in relation to the standards of both a drag performance and a political speech.